Pengaruh Kepemimpinan Transformasional dan Iklim Organisasi terhadap Kinerja Pegawai - Novita Tampi; Lalu Satria Utama; Dwi Putranto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this research is to find out the influence of transformational leadership and organizational climate together on employee performance at the Manokwari Class III Women's Penitentiary. This research uses a quantitative approach because it tests hypotheses objectively. This research was carried out at the Class III Women's Penitentiary in Manokwari. Data collection techniques include observation, interviews, and questionnaires using descriptive statistical data analysis techniques. The results of the research show that transformational leadership and organizational climate have a strong and significant influence on employee performance at the Class III Women's Penitentiary in Manokwari. In conclusion, transformational leadership and organizational climate influence employee performance at the Manokwari Class III Women's Penitentiary. Keywords: Employee Performance, Organizational Climate, Transformational Leadership